TI_GERICHTE 11.2017.42 vom 4. Mai 2017 , Restrizione della facoltà di disporre in virtù di un ordine dell'autorità - TI Tribunale d'appello (2017)
Restrizione della facoltà di disporre in virtù di un ordine dell'autorità